Altering carbon allocation in hybrid poplar (Populus alba × grandidentata) impacts cell wall growth and development. Issue 7 (4th March 2017) - Unda, Faride; Kim, Hoon; Hefer, Charles; Ralph, John; Mansfield, Shawn D.
Abstract: Galactinol synthase is a pivotal enzyme involved in the synthesis of the raffinose family of oligosaccharides (RFOs) that function as transport carbohydrates in the phloem, as storage compounds in sink tissues and as soluble metabolites that combat both abiotic and biotic stress in several plant species. Hybrid poplar (Populus alba × grandidentata ) overexpressing the Arabidopsis thaliana GolS3 ( AtGolS3 ) gene showed clear effects on development; the extreme overexpressing lines were stunted and had cell wall traits characteristic of tension wood, whereas lines with only moderate up‐regulation grew normally and had moderately altered secondary cell wall composition and ultrastructure. Stem cross‐sections of the developing xylem revealed a significant increase in the number of vessels, as well as the clear presence of a G‐layer in the fibres. Furthermore, AtGolS3‐OE lines possessed higher cellulose and lower lignin contents, an increase in cellulose crystallinity, and significantly altered hemicellulose‐derived carbohydrates, notably manifested by their mannose and xylose contents. In addition, the transgenic plants displayed elevated xylem starch content. Transcriptome interrogation of the transgenic plants showed a significant up‐regulation of genes involved in the synthesis of myo ‐inositol, along with genes involved in sucrose degradation. The results suggest that the overexpression of GolS and its product galactinol may serve as a molecular signal that initiates metabolic changes, culminating in a change in cell wall development and potentially the formation of tension wood.